Obstructive Sleep Apnea-Hypopnea Syndrome as a Risk Factor for Polycystic Ovary Syndrome: A Narrative Review of Prevalence, Pathophysiological Mechanisms, and Clinical Implications - Reza Deni Rohmansyah (Jurnal Health Sains, 2026)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine and metabolic disorders affecting women of reproductive age worldwide. Recent evidence indicates that Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) is frequently associated with PCOS and may contribute to worsening metabolic, hormonal, and reproductive dysfunctions. This study aimed to examine the role of OSAHS as a risk factor for PCOS by reviewing its prevalence, pathophysiological mechanisms, and clinical implications. This research employed a narrative review approach using relevant scientific literature obtained from PubMed, ResearchGate, and HHS Public Access databases. Articles discussing OSAHS and PCOS published in indexed journals were systematically analyzed to identify prevalence patterns, biological interactions, and therapeutic implications. The findings demonstrated that the prevalence of OSAHS in women with PCOS ranged from 20% to 37%, with higher incidence reported among obese and adult women. Several studies also identified a bidirectional causal relationship between OSAHS and PCOS. Pathophysiologically, intermittent hypoxia, oxidative stress, insulin resistance, inflammation, sympathetic activation, and hypothalamic-pituitary-gonadal axis dysfunction were found to contribute to hyperandrogenism, infertility, and increased cardiovascular risk. In conclusion, OSAHS plays a significant role in aggravating PCOS manifestations, highlighting the importance of early screening and comprehensive management to improve metabolic and reproductive outcomes in affected women.